EVALUASI ANTARMUKA PERMAINAN 3D BALAP KARUNG MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Adi Sucipto; Anugrah Dwirangga; RM. Joko Priyono (Universitas Nusa Cendana, 2023)
Traditional games are a form of knowledge passed down from generation to generation. An example of a traditional game is Balap Karung. Currently, many game developers have created the